Consequences of global warming - Zuñiga Herera, Levis Maria (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
This article makes known the and consequence of global warming on Earth, the measures that we must implement to mitigate this climate change that affects the planet more every day and causes major disasters, putting human life, fauna and flora at risk, which brings with it many variations that cause diseases and problems in daily life and aspects of survival. We must become aware of the seriousness of this phenomenon and work to mitigate as much as possible the effect that global warming causes more and more every day, as well as recognize that there is only one planet and we can only inhabit it, therefore we must take care of it. The human being has been one of the main causes of this significant increase in climate change through industries without measuring the consequences of these acts as well as the poor management that has been given for years to the fauna and flora, thus causing great disasters raising temperatures with carbon dioxide produced by man that are reflected on the planet through heat waves, droughts, strong storms, food shortages, death of animals.